Engineering photonic band gap in 1D phonic crystals using fresnel coefficients and comparing with the results of transfer matrix meghod - A Rahmatnezamabad; S Roshanentezar; H Afkhami; B Rahmatnezamabad (Iranian Journal of Physics Research, 2014)
In this paper photonic band gaps of 1D photonic crystal are compared by using transfer matrix method and Fresnel coefficients method. In Fresnel coefficients method, the refractive indices of each layer and incidence light angle to the surface are used for calculating Fresnel coefficients, and then the necessary and sufficient condition for a 100% reflection from the surface of double layer dielectrics is applied in such a way that reflection coefficient tends to unity so that photonic band gaps are determined. But in transfer matrix method there are some complications needed for solving quadratic partial differential equations and applying continuity of tangent components of fields and Bloch’s condition, though the results are the same